ISTIKHDAM AT-TARJUMAH AL-MUTANAKILAH FI SUFUF LUGHAH AL-‘ARABIYYAH FI AT-TA‘LIM AL-‘ALI - Azisi (Universitas KH. Mukhtar Syafaat, 2025)
This study aims to explore the implementation of translanguaging in Arabic language teaching at the higher education level, focusing on the development of four language skills: listening, speaking, reading, and writing. The research employed a qualitative method with a case study approach, involving observations and interviews with an instructor teaching an intensive Arabic language program. The findings indicate that translanguaging serves as a significant cognitive strategy in assisting students to understand the structure and vocabulary of the Arabic language, particularly for those with diverse language backgrounds. Students who engaged in translanguaging during their learning process demonstrated significant improvements in their listening and speaking skills, as well as their ability to organize their thoughts more effectively when writing. Furthermore, the study found that the use of a second language as a supportive tool not only enhanced students' comprehension but also increased their engagement in the learning process. Thus, the application of translanguaging in Arabic language teaching at higher education can create a more inclusive and effective learning environment. This research recommends that educational institutions provide training for educators to effectively implement translanguaging in the classroom.